Soil desiccation of different microtopographies on a slope in the loess area of northern Shaanxi, China - Qingping Gou; Qingke Zhu; Juan Chen (PLoS ONE, 2025)
The Loess Plateau is characterized by serious soil erosion, and different microtopographies are formed on the slopes under the action of gravity erosion and water erosion. Climate change and human activities have exacerbated the formation of soil dry layers on the Loess Plateau, and there are fewer studies on the soil desiccation of different microtopographies on the slopes. In this study, the different microtopographies on a slope typical of the loess area in northern Shaanxi Province were selected as the research object, using the undisturbed slope (US) as a reference, the soil moisture, soil water vertical profile distribution characteristics and soil desiccation of the 0–10 m soil layer of the different microtopographies on a slope were analyzed. The results showed that: the difference of shallow soil moisture in different microtopographies on a slope surface was not significant, the difference of deep soil moisture was significant, and the soil moisture overuse was the largest in the gully (GU), amounting to 386.36 mm, and the smallest in the ephemeral gully (EG) (131.02 mm); the GU, the sink hole (SH), and the scarp (SC) showed a trend of decreasing and then increasing with the increase of soil depth, and the platform (PL) has little overall trend of change in soil moisture with the increase of soil depth, and the soil moisture of US and EG shows the trend of “decreasing-then increasing-then decreasing” with the increase of soil depth. The drying intensity of different microtopographies on a slope surface: GU (34%)> SC (34%)> SH (23%)> PL (18%)> EH (13%)> US (12%), which may be due to a combination of factors such as microtopography altering ecological factors (e.g., soil moisture, light, etc.) and vegetation distribution patterns. In the future vegetation restoration process, the influence of microtopography should be fully considered to realize the sustainable development of forest and grass construction.